Design and simulation of two-stage CMOS amplifier for MEMS resonator - Mohd Taufik, Muhammad Syamsi; Zainuddin, Ahmad Anwar; Nordin, Anis Nurashikin; Pandian, Mohanraj Saundara (Institute of Electrical and Electronics Engineers, Inc., 2013)
The future integrated circuit would demand a combination of micromechanical components and traditional electronics. MEMS resonator is the one of future integrated circuit. MEMS resonators can provide CMOS compatibility and multifrequency operation on a single chip. In this paper, Two-Stage CMOS op amp for a MEMS-based oscillator is presented. The design of two-stage CMOS op amp is critically discussed. The op amp achieves a gain of 21 dB at VDD of 1.8 V and VSS of -1.8 V. The two-stage CMOS op amp is combined with 10 Mhz CC-beam resonator to create an oscillator at the frequency of ~10MHz with gain of 16dB. The oscillator is simulated using Cadence.